Disruption of Lipid Bilayers of Stratum Corneum by Transdermal Delivery of Glipizide in Microemulsion and Binary Co-solvent Systems: Disruption of Lipid Bilayers of Stratum Corneum - Nnadi, Charles O; Okorie, Ndidiamaka H; Mbah, Chika J (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The study was designed to develop and characterize structured vehicles for effective delivery of glipizide (GPZ) through excised stratum corneum (SC). Several mixed binary systems of ethanol or propylene glycol (PG) were prepared by homogeneous mixing with double distilled water. Different microemulsions were prepared by titration method and their physicochemical properties determined. Transdermal permeation of GPZ was studied in-vitro using modified Franz diffusion cells. Apart from the slight difference in their pH values, there was no significant difference in the physicochemical properties of the drug-loaded coconut oil-based microemulsions and their blank counterparts. Transdermal flux was highest in binary mixtures of 9:1 (v/v) aqueous ethanol (Jss 30.25 ± 5.75 μg/cm2h) and PG (Jss 6.34 ± 1.29 μg/cm2h) compared to their lower strengths. Transdermal GPZ flux, Jss, μg/cm2h was higher in o/w (121.2 ± 9.98) compared to w/o (3.89 ± 0.19) microemulsions with enhanced permeation of ≥ 23 fold using patch size of 10.45 cm2. Biophysical analysis of untreated and treated SC showed that GPZ permeation could depend on the extent of disruption of lipid and protein bilayers of SC by the vehicles. Cremophor RH 40/ethanol/coconut oil-based o/w microemulsion and 9:1 v/v mixed binary systems of ethanol or PG are promising vehicles for delivery of GPZ transdermally. Dhaka Univ. J. Pharm. Sci. 19(1): 29-35, 2020 (June)